Low-Cost Real-Time Monitoring for Enhanced Efficiency in PV Systems - Abdelkrim Rouabhia; Rachid Dabou; Abdelkader Abderrahmane; Abderrezzaq Ziane; Ahmed Bouraiou; Seyfallah Khelifi; Nordine Sahouane; Ammar Necaibia; Mohamed Blal (Revue des Énergies Renouvelables)
In this paper, we successfully created a low-cost, facile and reliable solution for real-time monitoring of grid-connected photovoltaic (PV) system. Our solution simplifies the connection and access to database of system performances, dependent on various parameters and environmental conditions. The real-time monitoring enables swift fault rectification, enhancing system efficiency, and providing insights into energy consumption of the PV system. We implemented our solution using low-cost electronic devices and sensors connected to 1.75 kW PV system installed in Adrar city situated in the Saharan region of southern Algeria. The electrical characteristics were measured using multiple sensors and stored in SD memory card and in server. Following the design and implementation of our data acquisition system for monitoring parameters from grid-connected photovoltaic system, we conducted a comparative study with the Fluke 2635A HYDRA Series II data acquisition system. The proposed system can be easily scaled to monitor higher power and larger PV stations with minimal adjustments by changing the high-range sensors and their parameters in the software.